3D Single‐Molecule Imaging of Transmembrane Signaling by Targeting Nanodiamonds. (7th December 2015) - Liu, Wenliang; Yu, Fenglei; Yang, Jianbo; Xiang, Bo; Xiao, Peng; Wang, Li
Abstract : Fluorescent nanodiamonds (FNDs) have recently emerged as promising probes for imaging applications. A significant limitation of the applications is the use of FNDs as endogenous protein tags for long‐term 3D single molecule imaging to gain critical understanding of the underlying mechanism such as transmembrane signaling. Here, FNDs conjugated with transforming growth factor (TGF) are developed as an imaging probe for endogenous TGF‐beta (TGF‐β) receptor labeling and 3D single molecule imaging. FNDs display higher localization accuracy in 3D than organic dye making it an ideal candidate for nanoscopy applications. The real‐time dynamics of TGF‐β receptors after binding conjugated FNDs and in cells treated with therapeutic small molecule kinase inhibitors (SMI) are further monitored. The Bayesian treatment of hidden Markov models confirms and quantifies three different diffusive states and the transition rates between the three states. The kinetic reaction favors a faster diffusion population after therapeutic SMI treatment. The results show that immobilized TGF‐β is critical for active signaling. SMI treatment can release TGF‐β from the signaling complex. The results demonstrate the reported method that provides a powerful technique to study the mechanism of transmembrane signaling and valuable insights for developing better therapeutic for TGF‐β‐associated cancers. Abstract : Fluorescent nanodiamonds conjugated with tumor growth factor (FND‐TGF) are developed for TGF‐β receptors labeling and 3D single molecule imaging in live cells. The real‐time dynamics of TGF‐β receptors after binding conjugated FNDs and treated with therapeutic inhibitors are revealed. The developed technique can be a powerful tool to investigate how the drug influences the target protein dynamic behaviors in live cells.